MEASUREMENT NON-INVASIVE HEMOGLOBIN WITH SMARTPHONE BASED - Hamrin
Anemia is a condition where the number of red blood cells or the hemoglobin concentration within them is lower than normal, leading to a reduced capacity of the blood to carry oxygen to body tissues. Hemoglobin plays a crucial role in transporting oxygen from the lungs to body tissues, which is essential for metabolism and energy production. According to the World Health Organization (WHO), the primary cause of anemia is nutritional deficiencies, particularly iron deficiency, but it can also result from a lack of folate, vitamin B12, vitamin A, or infectious diseases such as malaria, tuberculosis (TB), HIV, and parasitic infections. WHO identifies anemia as a significant global public health issue, especially for children and pregnant women. It is estimated that 42% of children under five years old and 40% of pregnant women worldwide suffer from anemia. In Indonesia, data from Riskesdas 2013 shows that the prevalence of anemia among women aged 15 years and older is 22.7%, while the prevalence among pregnant women is 37.1%. According to Indonesian Ministry of Health Regulation No. 736a/Menkes/XI/1989, a person is diagnosed with anemia if their hemoglobin level is below normal less than 13.0 g/dL for adult men, less than 12.0 g/dL for adult women, and less than 11.0 g/dL for pregnant women. Anemia is generally detected invasively by measuring hemoglobin levels in the blood, which can cause discomfort, generate medical waste, and pose disposal challenges. A non-invasive alternative for detecting anemia involves examining the lower eyelid (conjunctiva).